Integrating Qualitative and Quantitative Methods to Evaluate Performance of the Brazilian Network for Continuous Global Navigation Satellite System (GNSS) Monitoring (RBMC) - Antoun Netto, Sergio Orlando; Fortunato, Bruna Quintan; Bonato, André Geffer (Anuário do Instituto de Geociências, 2022)
We discuss a qualitative analysis of the efficiency of the Brazilian Network for Continuous Global Navigation Satellite System Monitoring (RBMC) using the Complex Holographic Assessment of Paradoxical Problems method (CHAP²), whose premise is the organization of intersubjectivity facilitated by the use of visual representation of structured knowledge (conceptual mapping) to increase the degree of consciousness to manage the paradoxes resulting from the complexity of living systems. We also describe a quantitative evaluation using Data Envelopment Analysis (DEA) allowing a ranking in terms of efficiency for further assessment by a professional of the area. The outcome of this study would be useful for IBGE (Brazilian Institute of Geography and Statistics) managers to be aware, for instance, of the suppliers and manufacturers of equipment available (receiver and geodetic antenna, Internet connection and constant supply of electricity) in efficient and ineffective stations, to guide new acquisitions, among other applications.